Titanium dioxide coated carbon nanofibers as a promising reinforcement in aluminum matrix composites fabricated by liquid pressing process. (February 2016) - Jo, Ilguk; Cho, Seungchan; Kim, Heebong; Jung, Byung Mun; Lee, Sang-Kwan; Lee, Sang-Bok
Abstract: Carbon-nanofiber (CNF) reinforced aluminum (Al) matrix composites were fabricated by a unique liquid pressing process. The mechanical properties of the CNF–Al composites, both with and without titanium dioxide (TiO2 ) coating layers on the CNF surface, have been studied. The compressive yield strength of the TiO2 coated CNF–Al composite dramatically increased (over nine times), as compared with that of an Al alloy. TiO2 coated CNFs are expected to be a highly sustainable and dispersible reinforcement for metal matrix composites (MMCs) that are fabricated by a metal melting process. Graphical abstract: